Internal and External Antecedents of Process Innovation: A review and extension - Walker, Richard M. (Public management review, 2014)
Innovation in public organizations is widely documented and has increasingly been the subject of empirical scrutiny. This article integrates the empirical evidence of the internal and external antecedents of process innovations in local governments and proposes directions for future research. The importance of the internal antecedents of organizational size, administrative capacity and organizational learning is uncovered using the meta-analytic support score method, but not in relation to external antecedents. Directions for further research are presented on the independent, joint and non-linear effects of antecedents on the adoption of innovation, and the implications of these arguments on the future study of innovation in local governments are considered from a structural contingency perspective.